Association between loss of bone mass due to short sleep and leptin-sympathetic nervous system activity. (May 2017) - Kuriyama, Nagato; Inaba, Masaaki; Ozaki, Etsuko; Yoneda, Yutaro; Matsui, Daisuke; Hashiguchi, Kanae; Koyama, Teruhide; Iwai, Komei; Watanabe, Isao; Tanaka, Rika; Omichi, Chie; Mizuno, Shigeto; et al.
Highlights: Short sleep was associated with a decline in cortical bone thickness. Short sleep was associated with sympathetic nervous system hyperactivity. Leptin levels were associated with cortical bone thickness in the short sleep group. Cortical bone mass may be regulated via interaction with the leptin-sympathetic nervous system under short sleep. Abstract: Background: Sleep has been reported to be an important factor in bone metabolism, and sympathetic nervous system activity has been reported to regulate bone metabolism. In this study, we evaluated the association between sleep, sympathetic nervous system activity, and bone mass. Methods: The study subjects were 221 individuals (108 males; 113 females; mean age: 55.1 ± 7.0 years) divided into two groups: those who slept for less than 6 h a day (short sleep [SS] group), and those who slept 6 h or longer (normal sleep [NS] group). The groups were compared with regard to lifestyle, cortical bone thickness, cancellous bone density, bone metabolism markers, blood leptin levels, and sympathetic nervous system activity as evaluated by heart rate variability analysis. Results: Significant differences were observed between the two groups in cortical bone thickness, blood TRACP-5b, and leptin levels. The L/H ratio (an index of sympathetic nervous system activity) was higher in the SS group than in the NS group. Significant negative correlations were observed between cortical bone thickness and both the L/H ratio and leptin levels, and a significant positive correlation was observed between the L/H ratio and leptin levels. Conclusions: Short sleep was associated with a decline in cortical bone thickness due to the promotion of bone resorption and sympathetic nervous system hyperactivity in the middle-aged group. Leptin levels and cortical bone thickness were found to be closely related, suggesting that cortical bone mass may be regulated via interaction with the leptin-sympathetic nervous system.